Pelatihan Pengelolaan Sampah Rumah Tangga Menjadi Pupuk Organik Cair Di Desa Karang Bawang, Banyumas - Norma Eralita; Yudi Agus Setiawan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Waste management in Karang Bawang Village is only transported by garbage officers, garbage transportation is carried out once a week or twice still using the transportation system, then disposed of to the landfill. The problem found in Karang Bawang Village is that there is organic waste that is disposed of carelessly and not managed specifically so that the waste causes environmental problems such as unpleasant odors, damaging the scenery, as a hotbed of disease and others. One way of processing waste is by processing the waste into liquid organic fertilizer. Liquid organic fertilizer (POC) is a solution resulting from the decay of organic materials derived from crop residues, household waste, animal urine, animal and human waste. In this community service activity, a training method for making liquid organic fertilizer was carried out with PKK women in Karang Bawang Village. The results of this community service can increase knowledge for PKK mothers to be able to utilize the remains of household waste to make liquid organic fertilizer which can be used to fertilize plants. And as an effort to utilize abundant household waste and reduce household waste in the community.